1999
DOI: 10.1897/1551-5028(1999)018<1149:eooeab>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Enrichment and Burrowing Activity of the Polychaete Neries Diversicolor on the Fate of Tetrachlorobiphenyl in Marine Sediments

Abstract: Abstract-The effects of organic enrichment and burrowing activity of the infaunal polychaete Nereis (Hediste) diversicolor on the distribution of 14 C-3,3Ј,4,4Ј-tetrachlorobiphenyl (TCB) were studied in an experimental benthic system. Organic enrichment of the sediment was provided by a mixture of the diatom Skeletonema costatum and the sea lettuce Ulva lactuca. Organic matter and TCB were both initially added to a surface sediment layer of the microcosms. A factorial design with organic enrichment (control vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…This is in agreement with previous studies, which have shown that assimilation efficiency and bioaccumulation of cadmium is greater from phytoplankton than from sediment (Griscom et al, 2002b) and wood fibers (Maloney, 1996). Similarly, several HOCs have been observed to exhibit enhanced bioaccumulation when associated with labile OM (Gunnarsson et al, 1999a(Gunnarsson et al, , 1999b. Since all species studied in this experiment can be assumed to have a preference for labile algae compared to more refractory food sources (Christensen and Kanneworff, 1985;Wheatcroft, 1989, Byrén et al, 2002), the higher BAFs for both…”
Section: The Role Of Organic Matter For Bioaccumulation Of Contaminantssupporting
confidence: 92%
“…This is in agreement with previous studies, which have shown that assimilation efficiency and bioaccumulation of cadmium is greater from phytoplankton than from sediment (Griscom et al, 2002b) and wood fibers (Maloney, 1996). Similarly, several HOCs have been observed to exhibit enhanced bioaccumulation when associated with labile OM (Gunnarsson et al, 1999a(Gunnarsson et al, , 1999b. Since all species studied in this experiment can be assumed to have a preference for labile algae compared to more refractory food sources (Christensen and Kanneworff, 1985;Wheatcroft, 1989, Byrén et al, 2002), the higher BAFs for both…”
Section: The Role Of Organic Matter For Bioaccumulation Of Contaminantssupporting
confidence: 92%
“…than with refractory lignin. Enrichment with high quality organic matter (OM) has been reported to stimulate accumulation of sediment associated PCB and PAH in various sediment dwelling marine invertebrates including A. filiformis and N. diversicolor (Gunnarsson, Schaanning, Hylland, Sköld, Eriksen, Berge et al, 1996, Gunnarsson et al, 1999b, Gunnarsson & Sköld, 1999. In all of these studies, however, enriched treatments contained more total organic carbon (TOC) than controls, thus confounding effects of SOM quality and quantity and complicating mechanistic interpretations.…”
Section: Bioaccumulation Of Pyrenementioning
confidence: 99%
“…Pyrene is a particle reactive compound , log K OW between 4.50 and 5.32 (Meador et al, 1995), and its distribution is thus highly dependent on forces affecting particle mixing, such as macrofaunal feeding and burrowing. Species-specific differences in bioturbation behaviour often appear to leave finger prints in the distribution of contaminants in the sediment (Holmer et al, 1997, Kure & Forbes, 1997, Gunnarsson et al, 1999a, Gunnarsson et al, 1999b, Sandnes, Forbes, Hansen & Sandnes, 2000. N. diversicolor build, and continuously re-route, extensive burrow galleries (Davey, 1994), while A. filiformis, although sometimes observed to be highly mobile, construct only as much burrow needed for keeping disks buried at ~5 cm depth with 2-4 arms protruding from the sediment for feeding (Woodley, 1975, Jonsson, Broman, Gunnarsson, Lagergren, Larsson, Ohlsson et al, 1997 ( Fig.…”
Section: Sedimentary Distribution Of ?Pyrenementioning
confidence: 99%
See 1 more Smart Citation
“…A. filiformis has further been shown to concentrate particle reactive contaminants such as fluoranthene and tetrachlorobiphenyl (TCB) in the burrow sediment, with TCB concentrations an order of magnitude higher in burrows compared to the surrounding bulk sediment (Gunnarsson et al 1999a, Selck et al 2004. N. diversicolor have been shown to do the same, however, to a lesser extent (Gunnarsson et al 1999b). The lower TCB concentrations observed in N. diversicolor burrows may result from contaminant dilution as the wall surface area of a single N. diversicolor burrow is several times larger than that of a single A. filiformis burrow.…”
Section: Burrow Sedimentmentioning
confidence: 99%